2000
DOI: 10.1161/01.atv.20.1.10
|View full text |Cite
|
Sign up to set email alerts
|

Oligoclonal T Cell Expansions in Atherosclerotic Lesions of Apolipoprotein E–Deficient Mice

Abstract: Abstract-T cells are present in atherosclerotic lesions at all stages of development. They exhibit activation markers and are particularly prominent at sites of plaque rupture. This suggests that T-cell-mediated immune responses are involved in the pathogenesis of atherosclerosis. Antigen-specific T cells reactive with oxidized lipoproteins and heat shock proteins have been isolated from plaques, indicating that local activation and clonal expansion might occur. To analyze different stages of atherosclerosis, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
108
0
7

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(125 citation statements)
references
References 42 publications
7
108
0
7
Order By: Relevance
“…The question of clonality of resident T cells in atherosclerotic lesions has also been addressed, with contrasting results. Initial data pointed to a polyclonal origin for T cells in plaques (45,46), but more recent studies demonstrated that resident T cells were locally activated by OxLDL and heat shock protein, using a restricted TCR repertoire (47,48).…”
Section: Discussionmentioning
confidence: 99%
“…The question of clonality of resident T cells in atherosclerotic lesions has also been addressed, with contrasting results. Initial data pointed to a polyclonal origin for T cells in plaques (45,46), but more recent studies demonstrated that resident T cells were locally activated by OxLDL and heat shock protein, using a restricted TCR repertoire (47,48).…”
Section: Discussionmentioning
confidence: 99%
“…In pioneering studies on ApoE-deficient mice under high cholesterol diet, the presence of iNKT cells was suggested by RT-PCR [13,14,32]. However, to date, iNKT cells have neither been isolated from plaques nor functionally characterized.…”
Section: Discussionmentioning
confidence: 99%
“…TCR Vb CDR3 spectratype analysis CDR3 spectratype analysis of TCR b-chain was performed as described (31). Briefly, RNA was extracted from purified donor-origin splenic CD3 + T cells of BMT mice.…”
Section: Cd8mentioning
confidence: 99%
“…cDNA was synthesized by using oligo(dT) primer and SuperScript II reverse transcriptase (Invitrogen). PCR was performed with a forward primer specific for one of the 14 TCR Vb families along with a constant Cb reverse primer labeled with fluorescent FAM, as previous described (31). The size distribution of each fluorescent PCR product was analyzed on a genetic analyzer (ABI3730; Applied Biosystems) using GeneMarker software.…”
Section: Cd8mentioning
confidence: 99%